Appetitive olfactory learning and memory in the honeybee depend on sugar reward identity - Simcock, N; Gray, H; Bouchebti, S; Wright, G (Elsevier, 2017)
© 2017 The Authors One of the most important tasks of the brain is to learn and remember information associated with food. Studies in mice and Drosophila have shown that sugar rewards must be metabolisable to form lasting memories, but few other animals have been studied. Here, we trained adult, worker honeybees (Apis mellifera) in two olfactory tasks (massed and spaced conditioning) known to affect memory formation to test how the schedule of reinforcement and the nature of a sugar reward affected learning and memory. The antennae and mouthparts of honeybees were most sensitive to sucrose but glucose and fructose were equally phagostimulatory. Whether or not bees could learn the tasks depended on sugar identity and concentration. However, only bees rewarded with glucose or sucrose formed robust long-term memory. This was true for bees trained in both the massed and spaced conditioning tasks. Honeybees fed with glucose or fructose exhibited a surge in haemolymph sugar of greater than 120 mM within 30 s that remained elevated for as long as 20 min after a single feeding event. For bees fed with sucrose, this change in haemolymph glucose and fructose occurred with a 30 s delay. Our data showed that olfactory learning in honeybees was affected by sugar identity and concentration, but that olfactory memory was most strongly affected by sugar identity. Taken together, these data suggest that the neural mechanisms involved in memory formation sense rapid changes in haemolymph glucose that occur during and after conditioning.